2020
DOI: 10.2147/ott.s241640
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-153-5p Enhances the Sensitivity of Triple-Negative Breast Cancer Cells to Paclitaxel by Inducing G2M Phase Arrest</p>

Abstract: Background: Paclitaxel (PTX) resistance is a main obstacle for the treatment of triplenegative breast cancers (TNBC). Evidences have shown that miR-153-5p could induce the apoptosis of breast cancer cells. Thus, this study aimed to investigate the effect of miR-153-5p on PTX-resistance TNBC cells. Methods: Cell Counting Kit-8, flow cytometry and wound healing assays were used to detect the viability, apoptosis and migration of MDA-MB-231/PTX cells, respectively. The luciferase reporter assay was used to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Many studies have shown that miR-153-5p, as a tumor suppressor gene, contributes to the development of various malignant tumors. Overexpression of miR-153-5p has been shown to enhance the drug sensitivity of breast cancer cells to paclitaxel, inhibit the proliferation and migration of breast cancer cells, and promote apoptosis of breast cancer cells 35 . In another study, miR-153 expression was lower in ovarian cancer than in adjacent tissues, which inhibited the proliferation and invasion of ovarian cancer cells and decreased their tumorigenesis potential 36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that miR-153-5p, as a tumor suppressor gene, contributes to the development of various malignant tumors. Overexpression of miR-153-5p has been shown to enhance the drug sensitivity of breast cancer cells to paclitaxel, inhibit the proliferation and migration of breast cancer cells, and promote apoptosis of breast cancer cells 35 . In another study, miR-153 expression was lower in ovarian cancer than in adjacent tissues, which inhibited the proliferation and invasion of ovarian cancer cells and decreased their tumorigenesis potential 36 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed recently that several miRNAs, such as miRNA-200a, miRNA-145, or miRNA-224, are expressed aberrantly in meningioma 8 . miRNA microarrays have demonstrated that abnormal miRNA expression may act as potential diagnostic and prognostic biomarkers for cancer 9,10 , and many potential miRNAs were used as diagnostic biomarkers and therapeutic targets for meningiomas [11][12][13] . MiR-153-5p is a newly discovered small-molecule coding RNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies have revealed that an increase in AKT expression can be contributed to downregulation of miR-153. However, overexpression of miR-153 induces cell cycle arrest in G0/G1 and G2/M phases as well as inhibiting proliferation by regulating the expression of AKT, CDK1 through binding to and degrading their mRNAs (3,23,24,26). Moreover, miR-153 suppresses the AKT signaling pathway in glioblastoma through reduction in expression of insulin receptor substrate-2 (Irs-2) which acts as a molecular adaptor, mediating influences of insulin and insulinlike growth factor 1 (IGF-1) on cell proliferation (Figure 1) (27).…”
Section: Role Of Mir-153 In Proliferation Of Cancer Cellsmentioning
confidence: 99%
“…However, high expression level of miR-153 increases sensitivity of cancer cells to radiotherapy, which may be mediated by targeting Snail and Jagged canonical notch ligand1 (J AG1) in panc reatic canc er (7 0, 71 ). Moreover, downregulation of miR-153 has been reported in drug resistant cancer cells, whereas miR-153 overexpression enhances the sensitivity of cancer cells to chemotherapy (26,35,76). One of the suggested mechanisms of drug resistance of cancer cells is upregulation of ABCE1 due to downregulation of miR-153 in lung cancer cells (72).…”
Section: Role Of Mir-153 In Radio and Chemotherapy Resistance Of Canc...mentioning
confidence: 99%